Knowledge, Attitudes, and Practices of ICU Medical Staff toward Nutrition Care and its Impact on Patient Recovery in Taiz, Yemen - Haitham T. S. Mohammed; Lamia A. S. Ali; Malak Anwar Saif; Nada Khalid Al-Adeemy; Noha Kamel Al-Nadhary; Raghad Sameer Saif; Shaima Kamel Al-Nadhary; Yomna Mukarram Al-Dobai; Nur Mufida Wulan Sari (Amerta Nutrition)
Background: Proper nutrition is essential for enhancing patient recovery, especially within hospital environments. ICU medical staff are instrumental in providing appropriate nutritional care, which significantly affects patients' health outcomes. However, in Yemen, the lack of knowledge for assessing nutritional requirements, and the importance of nutrients adequacy for patients underscores the importance of improving staff involvement in nutrition care quality management.